1951
DOI: 10.1136/bmj.2.4737.939
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Otorrhoea with Chloramphenicol

Abstract: The common causes of persistent ear discharge are chronic otitis media, chronic otitis externa, and infection in the cavities made by tympano-mastoidectomies and fenestration operations. It is difficult to assess the proportion of the population suffering from running ears, but Formby (1942) reported that just over 2% of recruits examined during the 1939-45 war were rejected because of chronic ear diseases. Otorrhoea formed the bulk of the cases. Johnston (1948) found that of 1,902 factory employees 3.3 % had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1952
1952
1982
1982

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These findings suggested that a histologic study to determine the topical ototoxicity of To make the investigation significant, it was necessary to: (1) set up adequate numbers of experimental and control animals; (2) use a concentration of the drug comparable to that used in clini¬ cal medicine; (3) use a control solution with a concentration and pH equal to that of the chloramphenicol solution; (4) use a relative¬ ly low dosage of the drug; (5) use it for a relatively brief period of time; (6) apply the drug in equal volumes and to the same area each time; and (7) use careful temporal bone preparation so that the end product, a his¬ tologie slide, would be meaningful.…”
Section: Si Ncementioning
confidence: 99%
“…These findings suggested that a histologic study to determine the topical ototoxicity of To make the investigation significant, it was necessary to: (1) set up adequate numbers of experimental and control animals; (2) use a concentration of the drug comparable to that used in clini¬ cal medicine; (3) use a control solution with a concentration and pH equal to that of the chloramphenicol solution; (4) use a relative¬ ly low dosage of the drug; (5) use it for a relatively brief period of time; (6) apply the drug in equal volumes and to the same area each time; and (7) use careful temporal bone preparation so that the end product, a his¬ tologie slide, would be meaningful.…”
Section: Si Ncementioning
confidence: 99%
“…When chloramphenicol 10 per cent, in propylene glycol was described by Lewis and Gray (1951), it was decided to compare the results of a series of cases treated with this solution with those of a series treated with B.I.P.P. The chloramphenicol results were so much superior, however, that all other forms of treatment were abandoned and now all the radical mastoidectomies are performed in the following manner.…”
Section: Cleansing Of the Cavitymentioning
confidence: 99%